Monoclonal Antibody Differentiation of Mycoplasma mycoides subsp. mycoides Small-Colony Strains Causing Contagious Bovine Pleuropneumonia from Less Important Large-Colony Strains - Rurangirwa, Fred R. (American Society for Microbiology, 2000)
Monoclonal antibody (MAb) PK-2 inhibited the in vitro growth of nine Mycoplasma mycoides subsp. mycoides small-colony strains. In contrast to the results with polyclonal antisera, growth inhibition by MAb PK-2 was specific for M. mycoides subsp. mycoides small-colony strains and constituted a reliable means of distinguishing them from other mycoplasmas.